2019
DOI: 10.5004/dwt.2019.24098
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing hydraulic zones of a vertical circulation well in presence of ambient flow

Abstract: a b s t r a c tAlthough vertical circulation well (VCW) has been widely applied for aquifer remediation and hydrogeological parameter estimation for three decades, few studies have focused on the hydraulic zone visualization, and the spatial scale of hydraulic zones as functions of VCW parameters. This study provided a numerical method to visualize 3D steady-state flow field induced by VCW in a confined aquifer in presence of an ambient flow. Mathematical model for velocity field is established based on the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The conceptual model of groundwater flow associated with a VCW system is shown in Figure 1. The assumptions are similar to those in the studies of Philip and Walter (1992) and Xia et al (2019) Equations 1-5 have analytical solutions of drawdown distribution as demonstrated in previous studies (e.g., Chen et al, 2010Chen et al, , 2011Sutton et al, 2000;Zlotnik & Ledder, 1996), where the specific discharge (or Darcy velocity) distribution can be calculated based on Darcy's law, and the following expressions;…”
Section: Groundwater Flow Modelmentioning
confidence: 92%
See 3 more Smart Citations
“…The conceptual model of groundwater flow associated with a VCW system is shown in Figure 1. The assumptions are similar to those in the studies of Philip and Walter (1992) and Xia et al (2019) Equations 1-5 have analytical solutions of drawdown distribution as demonstrated in previous studies (e.g., Chen et al, 2010Chen et al, , 2011Sutton et al, 2000;Zlotnik & Ledder, 1996), where the specific discharge (or Darcy velocity) distribution can be calculated based on Darcy's law, and the following expressions;…”
Section: Groundwater Flow Modelmentioning
confidence: 92%
“…The conceptual model of groundwater flow associated with a VCW system is shown in Figure 1. The assumptions are similar to those in the studies of Philip and Walter (1992) and Xia et al (2019) as follows. (1) The aquifer is confined, homogeneous, vertically anisotropic and horizontally isotropic, and radially infinite with a finite constant thickness.…”
Section: Groundwater Flow Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This report describes a number of contributions by the late B. Herrling and J. Stamm, inventors and patent holders for a vertical circulation well remediation technology for groundwater as well as by other researchers, for example, Herrling and Stamm (1992), Philip and Walter (1992), Chen and Knox (1997), Knox et al (1997), and many others. Tu et al (2020), along with Tu et al (2019) and Ni et al (2011), failed to acknowledge relevant post-1998 literature, including publications by Xia et al (2019), Kahler and Kabala (2018), Jin et al (2016), Chen et al (2010), Johnson and Simon (2007), and many others. Tu et al (2020), along with Tu et al (2019) and Ni et al (2011), missed applications of vertical circulation wells for aquifer characterization, and, in particular, contributions from this author, including Kabala and Xiang (1992), Kabala (1993), and others, as well as those from V. Zlotnik and co-workers, including Zlotnik and Ledder (1996), Peursem et al (1999), and others.…”
Section: Inadequate Literature Reviewmentioning
confidence: 99%